Conhecendo fractal no ensino médio: árvore pitagórica - Nicola, Celso Henrique (2013)
This work has objective to show results of a didactic experience that consider the use of a dynamic geometric software in a restrict area of the Mathematic, named fractal . This study presents a great complexity and beauty in your geometric structures. Therefore, we present some fractals, in particular, the Pythagorean Tree that arouses the interest of students. For geometric constructions, we chose the GeoGebra software, based in the geometry lessons that we had in the course. Next, we explore one of the most famous theorems of the Plane Geometry, the Pythagoras Theorem, in addition of others mathematics contents, such as, counting. We also study the main trends connected to the informatics and we took advantages of the computational technology resource to assist the students with the construction and learning, including them in a new educational scenario based in the technology presence.